ADDUCTOR LONGUS ACTIVATION DURING TWO COMMON HIP ADDUCTION EXERCISES. Issue 22 (1st November 2016) - Long, C; Light, N
Abstract : Various exercises are prescribed in the management of adductor-related groin pain. Isometric adductor ball squeeze exercises are commonly incorporated into both prevention and rehabilitation training, as is the Copenhagen Adduction exercise, which offers a more dynamic and challenging alternative. The adductor longus (AL) muscle is commonly indicated in adductor pathology and may be considered a 'target' tissue, yet there is minimal literature examining adductor muscle activation during such exercises. Understanding variation in levels of AL activation during differing exercises, may inform exercise selection. Nine healthy university football players completed a number of repetitions of adductor ball squeezes (45° hip flexion) and Copenhagen adductions, with surface electromyography (sEMG) measuring their AL activity. Results showed that isometric ball squeezes produced larger average AL activity than the Copenhagen adduction exercise (p<0.046). The ball squeeze exercise also demonstrated higher percentage of peak sEMG activity (33%) compared to the Copenhagen adduction exercise (26%). No statistically significant differences between peak sEMG values were observed. The results suggest that AL activation is higher during an isometric ball squeeze when compared with the Copenhagen adduction exercise, despite being a more dynamic and stressful exercise. This may be related to altered synergistic muscle recruitment and varying working muscle lengths, which have been shown to alter EMG activity levels. Adductor ball squeezes are safe, load adjustable and simple to instruct requiring no assistance. Subsequently, they remain ideally suited in various contexts, for example pre-activation exercises prior to activity (prevention) and during early phase loading post adductor related injury (treatment), where the Copenhagen adduction exercise is not indicated.